Intelligence is as intelligence does. Issue 4 (7th June 2018) - Stout, Mark; Warner, Michael
Abstract: Anglo-American scholars have sought to define 'intelligence' by positing that it helps leaders acquire and control information against competitors. Most or all agree that intelligence entails collection, analysis, and counterintelligence, and many add covert action as well. These core functions of intelligence, however, neglect the variety of activities that intelligence services have also engaged in, such as conducting diplomacy, guarding borders, running prisons, operating military units, designing atomic bombs, and managing professional soccer teams. Such peripheral functions can vary across time and place, while the core functions endure but can gradually grow in number over time. Simultaneously, non-intelligence agencies encroach on the turf of intelligence agencies. Thus, 'intelligence' is what intelligence agencies do. We close by wondering how these insights can generate testable hypotheses to illuminate patterns in intelligence functions and organizations over time and across a range of regimes.